Psychological Consequences in Patients With Amputation of a Limb. An Interpretative-Phenomenological Analysis - Roșca, Andra Cătălina; Baciu, Cosmin Constantin; Burtăverde, Vlad; Mateizer, Alexandru (Frontiers in Psychology, 2021)
The study aimed to identify the psychological changes that result from the amputation of a limb and the ways in which patients coordinate their daily lives. The study uses an interpretative phenomenological analysis (IPA) aimed at understanding individual experiences in seven patients who have suffered limb amputation. The method used consisted of individual, semi-structured interviews, conducted approximately four months after surgery, to patients at home or in hospital, at the time of their regular checkup. The interviews were audio recorded, transcribed and, following the qualitative analysis performed, six common themes were identified: emotional impact, negative affects, tendency towards isolation, role constraints and limitations, phantom limb and emotional balancing. A specific theme for patients who have suffered amputations is phantom limb pain, which has received special attention from researchers. The last topic relates to the tendency towards emotional balancing and psychological calibration to return to normal life.